Training and Experience of Nurses in Responding to Alcohol Misuse in Rural Communities. Issue 4 (14th February 2013) - Kennedy, Alison J.; Mellor, David; McCabe, Marita P.; Ricciardelli, Lina A.; Brumby, Susan A.; Head, Alexandra; Mercer‐Grant, Catherine
Abstract Objective Alcohol misuse by farmers continues to challenge rural nurses. This article reports on the experiences of Australian nurses participating in the Alcohol Intervention Training Program (AITP). Design and Sample Qualitative interviews of 15 rural and remote nurses. Measures Semi‐structured phone interviews were utilized to assess the response to and implementation of the AITP—an intervention designed to build nurses' knowledge, confidence and skills when responding to alcohol misuse. It comprises practical and theoretical components and was designed for rural and remote settings where nurses encounter alcohol misuse. Results Nurses found the training provided new—or built on existing—knowledge of alcohol misuse and offered practical hands‐on "real life" skills. A range of workplace and personal situations where the content of the training was now being utilized were identified, and future use anticipated. Barriers to using the new knowledge and skills included both rural and generic issues. Constructive feedback to increasingly target the training to rural settings was recommended. Conclusions The AITP is an effective training program. It can be further tailored to meet common needs of rural and remote nurses working with farmers who misuse alcohol, while recognizing diversity in rural practice.